We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
31
2
avatar

Solve the system x^2 = y + 2, y^2 = x + 2.

 Dec 1, 2019
 #1
avatar+22 
0

Do plugin

x = y^2-2

x^2 = (y^2-2)(y^2-2) = y^4-4y^2+4. So y^4-4y^2+4=y+2. Then y = y^4-4y^2+2. Begin to test values starting with 5 and getting smaller. For 5, it doesn't work. It is very far, so we try 3. For 3, we have 81 = 36+2 which is false. For 2, we have 2 = 16-16+2 which is true so y = 2 and x = 2 clearly.

 Dec 1, 2019
 #2
avatar+23542 
+1

Solve the system \(x^2 = y + 2,\ y^2 = x + 2\).

 

\(\begin{array}{|lrcll|} \hline (1) & x^2 &=& y+2 \quad \text{or} \quad \boxed{y = x^2-2} \\\\ (2) & y^2 &=& x+2 \\ & \left(x^2-2\right)^2 &=& x+2 \\ & x^4-4x^2+4 &=& x+2 \\ & x^4-4x^2-x+2 &=& 0 \\\\ \boxed{x_1= 2}: & x^4-4x^2-x+2 &\overset{?}=& 0 \\ & 2^4-4*2^2-2+2 &=& 0 \ \checkmark \\ & \text{Polynomial long division}: & \\ & (x^4-4x^2-x+2) &=& (x-2)(x^3+2x^2-1) \\\\ \boxed{x_2= -1}: & x^3+2x^2-1 &\overset{?}=& 0 \\ & (-1)^3+2(-1)^2-1 &=& 0 \ \checkmark \\ & \text{Polynomial long division}: & \\ & (x^3+2x^2-1) &=& (x+1)(x^2+x-1) \\\\ & x^2+x-1 &=& 0 \\\\ & x &=& \dfrac{-1\pm \sqrt{1-4(-1)}} {2} \\ & x &=& \dfrac{-1\pm \sqrt{5}} {2} \\ \boxed{x_3 = \dfrac{-1+\sqrt{5}} {2}} \\ \boxed{x_4 = \dfrac{-1-\sqrt{5}} {2}} \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline && y = x^2-2 \\\\ x_1=1 && y_1 = -1 \\ x_2 =2 && y_2 = 2 \\ x_3 = \dfrac{-1+\sqrt{5}} {2} && y_3 = \dfrac{-1-\sqrt{5}} {2} \\ x_4 = \dfrac{-1-\sqrt{5}} {2} && y_4 = \dfrac{-1+\sqrt{5}} {2} \\ \hline \end{array} \)

 

laugh

 Dec 2, 2019

23 Online Users

avatar
avatar